Perceptions, health seeking behavior and utilization of maternal and newborn health services among an indigenous tribal community in Northeast India: a community-based mixed methods study - León Cáceres, Ángela; Ramesh, Rohan Michael; Newmai, Puisaumaliu; Kikon, Rhondemo; Deckert, Andreas (Frontiers in Public Health, 2023)
BackgroundEvidence suggests that healthcare utilization among tribal communities in isolated regions can be influenced by social determinants of health, particularly cultural and geographical factors. The true mortality and morbidity due to these factors in remote tribal communities are often underestimated due to facility-dependent reporting systems often difficult to access. We studied the utilization of health services for maternal and newborn care and explored how cultural beliefs, perceptions, and practices influence the health-seeking behavior (HSB) of an indigenous tribal community in Northeast India.MethodsWithin a concurrent triangulation design, the combined results from 7 focus group discussions and 19 in-depth interviews, and the 109 interviews of mothers from a community-based survey were interpreted in a complementary manner. The qualitative data were analyzed using a conceptual framework adapted from the socio-ecological and three-delays model, using a priori thematic coding. Multivariable logistic regression was carried out to identify factors associated with home delivery.ResultsOnly 3.7% of the interviewed mothers received the four recommended antenatal check-ups in health centers, and 40.1% delivered at home. Mothers residing in the villages without a health center or one that was not operational were more likely to deliver at home. HSB was influenced significantly by available finances, the mother’s education, low self-esteem, and a strong belief in traditional medicine favored by its availability and religious affiliation. The community sought health services in facilities only in emergency situations, determined primarily by the tribe’s poor perception of the quality of health services provided in the irregularly open centers, locally available traditional medicine practitioners, and challenges in geographical access. National schemes intended to incentivize access to facilities failed to impact this community due to flawed program implementation that did not consider this region’s cultural, social, and geographical differences.ConclusionThe health-seeking behavior of the tribe is a complex, interrelated, and interdependent process framed in a medical pluralistic context. The utilization of health centers and HSBs of indigenous communities may improve when policymakers adopt a “bottom-up approach,” addressing structural barriers, tailoring programs to be culturally appropriate, and guaranteeing that the perceived needs of indigenous communities are met before national objectives.
Gesehen am 24.07.2023